ACCESSIBILITY: DISABLED PASSENGERS IN COMMERCIAL FLIGHTS IN INDONESIA - Y, Annalisa; MurzaL; Febrian; Nurhidayatuloh; Elmadiantini (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to determine the accessibility regulation of disabled passenger rights in commercial flights in Indonesia and to find the forms of violations committed by commercial airlines towards disabled passengers. This research is a normative study described in a qualitative descriptive form in accordance with the concept and scope of the problem under study. The approaches used are the statute approach, conceptual approach, and case approach. The results show that although the regulation of accessibility for persons with disabilities has been regulated in legislation, it does not yet reflect constructive norms related to disability accessibility where the regulation is more focused on physical disability compared to the intellectual, mental, and sensory disabilities. Meanwhile, the forms of violations committed by carriers towards persons with disabilities are unlawful acts which can rise to discrimination and cause harm to disabled passengers both in material and immaterial terms. Not achieving disability regulation in air transportation is one form of action that neglects passenger rights. For this reason, norms governing the rights of disabled passengers need to be more concrete and services to them need to be improved so that they have the same rights as non- disabled passengers.